"Selfie" harm: Effects on mood and body image in young women. (December 2018) - Mills, Jennifer S.; Musto, Sarah; Williams, Lindsay; Tiggemann, Marika
Highlights: We examined the behaviour of taking and posting "selfies" online. The current study used an experimental design. Posting selfies on social media resulted in worsened mood and body image. Even posting retouched selfies resulted in harmful effects. Abstract: "Selfies" (self-taken photos) are a common self-presentation strategy on social media. This study experimentally tested whether taking and posting selfies, with and without photo-retouching, elicits changes to mood and body image among young women. Female undergraduate students ( N = 110) were randomly assigned to one of three experimental conditions: taking and uploading either an untouched selfie, taking and posting a preferred and retouched selfie to social media, or a control group. State mood and body image were measured pre- and post-manipulation. As predicted, there was a main effect of experimental condition on changes to mood and feelings of physical attractiveness. Women who took and posted selfies to social media reported feeling more anxious, less confident, and less physically attractive afterwards compared to those in the control group. Harmful effects of selfies were found even when participants could retake and retouch their selfies. This is the first experimental study showing that taking and posting selfies on social media causes adverse psychological effects for women.